Las ideas sobre salud pública de los dirigentes liberales españoles en las Cortes de Cádiz (1810-1814) (2003)
ABSTRACT: Transcendental political episodes took place in Spain in the earliest nineteenth century. Between 1808 and 1814 the country was conducted by political decisions carried out by liberal leaders ruling the so named Cortes de Cádiz. Whose main proposal was to establish a constitutional government in replacement for the traditional absolutist regime. This process was interrupted by a period of absolutist government headed by King Fernando VII, extended from 1814 to 1820. However, the Cortes de Cádiz main ideas were retaken by the revolutionists that conducted a new period of constitutional government between 1820 and 1823. The Cortes de Cádiz are thus considered in the political scene as a necessary background to understand the institutional shaping of the liberal Spanish State along the nineteenth century. This article characterizes the main initiatives for reforming public health achieved by the Cortes de Cádiz. The main sources were the official publications of the Cortes de Cádiz and diverse writings related to our subject of interest published by the time. Additionally, we used some outstanding critical literature related to the period.